The Effectiveness of Phacoemulsification in Cataract Management: Procedures, Benefits, and Challenges - Nurhaliza, Rahma; Himayani, Rani; Febriani, Wiwi; Rudiyanto, Waluyo (CV. Jasa Sukses Abadi, 2025)
Cataract is a condition in which the eye's lens, initially clear becomes cloudy, obstructing the passage of light to the retina and causing vision impairments such as blurred vision, reduced visual acuity, and faded color perception. According to WHO data (2022), approximately 2.2 billion people worldwide experience visual impairment, with cataracts being the leading cause of reversible blindness. In Indonesia, the prevalence of cataracts is 1.8%, with an annual incidence rate of 0.1%, and 50% of blindness cases are caused by cataracts. Surgery is the only method to treat cataracts, with phacoemulsification being the most commonly used technique. Phacoemulsification is a cataract surgery technique that employs an ultrasonic tip to break down the cloudy lens, followed by aspiration of the lens fragments. This technique has numerous advantages, including smaller incisions, faster wound healing, good visual acuity outcomes post-surgery, and a lower risk of complications than other surgical methods.